The Owner Factor: An Innovation Element of Business Model Canvas by SMEs Rattan Industry in Cirebon Indonesia - Ida Hindarsah , Bambang Heru Purwanto , Sidiq Priadana; Adi Fahrudin (International Journal of Advanced Science and Technology, 2020)
Indonesia is the largest rattan producing country in the world. It is estimated that 80% of rattan raw material worldwide is produced by Indonesia, the rest is produced by other countries such as the Philippines, Vietnam and other Asian countries. In 2003-2006 the rattan industry in Indonesia experienced ups and downs with an average of 0.38% per annum and a decrease of an average of - 3.63% per year. Most of the rattan industry players are from West Java Province, to be exact from Cirebon. Small Medium Enterprises (SMEs) is one of the actor of this trading industry. Although some SMEs are experiencing collapsed due to intense competition in the globalization era. Nevertheless, there are still several SMEs that can survive to this day. So in this connection, the question arises of business model innovations such as what is done by rattan SMEs in Cirebon Regency in facing business competition in the globalization era? This paper using qualitative method to describe the innovation components applied by SMEs. The result shows that rattan industry SMEs in Cirebon Regency based on BMC approach they applied all the components and one component plus that is owner predisposing factor which is the basic behavior of the owner that will influence the application of the entire component of business model.